(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
We start this research from an analytical vision that combines the theoretical and practical aspect, and aims to study the concept of digital transformation and its economic and legal dimensions, with a special focus on its practical repercussions on commercial contracts in terms of conclusion, implementation and proof. The research also seeks to identify the challenges imposed by the modern digital environment, and discuss the legislative efforts made to keep pace with these variables, especially in the Kingdom of Saudi Arabia, which is witnessing rapid developments in the field of digitization and related legislation.